Development Defect: A Case Study on Destroying Indigeneity of Majhi Community - Panta, Saroj Raj (Dhaulagiri Journal of Sociology and Anthropology, 2022)
Majhis have coped with marginal resources in the Neoliberal economic context and are facing many problems. This article focuses on the Majhi people and their livelihood transformation from traditional occupation. The main objectives of this study are to explore the present condition of the Majhi people in Baglung and how they got into their traditional profession. This study adopts qualitative data based on observations, case studies, and in-depth interviews through primary and secondary sources of literature review. Majhi people have coped with marginal resources in the Neoliberal economic context and facing many problems. They usually change their traditional occupations to boating, selling firewood, gold mining, and fishing. There are forced to change their livelihoods due to globalization. Modern means of transportation and limited income are insufficient to fulfill their basic needs. They face social, economic, and physical difficulties in their daily lives. Globalization and modern modes of transportation present them with more challenges and fewer opportunities because of the construction of the Pokhara-Baglung highway. Majhi people have not been able to easily grasp opportunities for political, social, and educational changes due to a lack of education after abandoning their traditional occupation and living place due to the construction of Pokhara- Baglung highway. This paper will be valuable for policy maker and, future researchers, and academia as well.